Collective rights and digital content : the legal framework for competition, transparency and multi-territorial licensing of the new European directive on collective rights management /: the legal framework for competition, transparency and multi-territorial licensing of the new European directive on collective rights management. (2015) - Lucena, Cláudio
No abstract available